VIABILITAS BIJI BELIMBING (Averrhoa carambola L.) KULTIVAR ‘DEWA BARU’ ASAL KECAMATAN CIMANGGIS, DEPOK PADA BERBAGAI SUHU PENYIMPANAN - Agriana Ali (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
This research is aimed to determine the quality of carambola seed (Averrhoa carambola L.). Seeds have been taken from fruits with a range of ripening index of 5—6. The initial moisture content of seed was 40% on fresh weight basis with 92% initial germination. The seeds were dessicated to 32%, 25%, 18%, 11%, 4%, and stored at ambient (27–30 °C), cold (5 °C), and freezing temperature (-15 °C) for 4 weeks. Several parameters were measured, including the capability of seeds to germinate, maximal growth potential, length of hypocotyle, length of epicotyle and leaves (dimension). The seeds were found to be tolerant to dessication up to 4% moisture content in any storage temperature. The favourable storage temperature was cold (5 °C) with 40% moisture content and ambient (27–30 °C) with 25% moisture content.Keywords : Averrhoa carambola, seed germination, viability